Development of a miniaturized PZT-based MEMS Fabry-Perot interferometer with eutectic wafer bonding and its interface electronics - Tusher, Md Munirul Islam; Lee, Hyunho; Lee, Sanghoon; Lee, Keekeun (Sensors and Actuators A: Physical, 2024)
A miniaturized lead zirconate titanate (PZT)-actuated Fabry-Perot interferometer (FPI) was developed for an 850 nm light beam selection by modulating the air gap between two refractive mirrors. The developed FPI consists of mirrors, a PZT actuator for air gap modulation, metal electrodes, and interface electronics capable of applying a square voltage at a frequency of 0.1 Hz. Eutectic wafer bonding method was employed to bond two mirrors through rapid thermal annealing (RTA) and applying mechanical pressure for a short time to minimize the interdiffusion between layers. The PZT actuator and metal electrodes serve as a thickness spacer to create an air gap between the two mirror plates. Alternating high and low dielectric layers (TiO2 and SiO2) with precise thickness and high crystallization quality were utilized for the formation of the refractive mirror because these layers offer high reflectivity and low absorption loss, enabling effective transmission of a specific wavelength in the incident light beam. By applying 0.1 Hz square pulses to the PZT actuator, the air gap was modulated, resulting in significant shifts in the center wavelength of the filtered beam at the desired wavelength. The study demonstrates the successful modulation and optimization of transmission peaks, ensuring a sharp full width at half maximum (FWHM) and high transmission rate. It also provides comprehensive experimental process factors for optimizing heat treatment conditions for PZT and refractive mirrors, minimizing metal interdiffusion between the dielectric layers, and ensuring mirror plate flatness. The device parameter effects such as cavity length orders, sequence of refractive indices for dielectric layers, and the extent of elongation of PZT with applied voltage were systematically studied to achieve optimal performance of FPI filter. The developed interface electronics allow voltage modulation up to 21.9 V at a frequency of 0.1 Hz, while preserving the elasticity of the PZT actuator.
Keywords: Air-gaps; Dielectric layer; Eutectic bonding; Fabry-perot interferometer; Interface electronics; Metal electrodes; PZT; PZT actuator; Refractive mirror; Wavelength modulation; Eutectic bonding; Fabry-Perot interferometer (FPI); Interface electronics; PZT; Refractive mirror; Wavelength modulation